Festival de Parintins: os bastidores da ópera cabocla - Sena, Djane da Silva (2022)
The Parintins Festival is a popular celebration where the Bois Garantido and Caprichoso duel in a great open-air show in the middle of the Amazon rainforest. In the arena called Bumbodromo, characters and imaginary elements, from Amazonian legends and indigenous rituals, act as the guiding thread of the show that today is the largest popular manifestation in Northern Brazil and which takes place on the last weekend of June. Taking as a starting point my childhood memories, stories that my grandmother told, this work has as main objective to problematize the backstage of the Festival using as a time frame, the study of the transformations in the period from 1988 to 2019 from the perspective of those who build the Festival, but do not appear. By studying the stages of the creative process (design, production and execution), we analyze their contribution to the maintenance of the Festival as a manifestation of popular culture. By giving voice to these cultural agents who, like my grandmother, were and are, an integral and important part of the maintenance of this show, we want to contribute to research in the field of Popular Cultures and the Parintins Festival itself, which is seen by many as a mere product of the culture industry. Using my grandmother's stories as a guiding thread, we built a tool for analysis in the construction of the narratives that are staged in the bumbodromo. Making use of the semiotics of culture as a theory and method, we describe the systems and subsystems of the Semiosphere of the Festival de Parintins and, thus, we identify the characters that make up this research. In order to understand the dynamics and evolution of this popular manifestation, we resort to the theoretical and conceptual foundations of the Ethnocenology of Armindo Bião, Cherisf Kasnadar and Jean Marie Pradier. To discuss the Parintins Festival from cultural studies, we use the concepts of Ortiz, Burke, Hall and Canclini. As methodological support, we used participatory qualitative research, in addition to semiotic analysis to map the semiosphere of the Parintins festival with its systems and subsystems. About the main and secondary characters of this process, we guarantee their place of speech using open interviews, adopting the method of participant observation, meeting all safety standards due to the Covid-19 pandemic and the Research Ethics Council - CEP.